Influence of age, gender, and prodromal symptoms on sudden death in a tertiary care hospital, eastern Saudi Arabia - Houssien Kamal Nofal; Mohammed Fakhry Abdulmohsen (Wolters Kluwer Medknow Publications, 2010)
Background: Sudden death (SD) remains an important worldwide public health problem. The incidence of SD and causes vary in different societies, and these differences are influenced also by demographic and clinical factors such as age, gender and prodromal symptoms and signs. This six-year study describes the influence of these factors on SD. Materials and Methods: This is a retrospective study of SD in all age groups undertaken in King Fahd Hospital of the University (KFHU), Eastern Saudi Arabia. All cases of death (1273 total, 1050 expected death and 223 cases of sudden unexpected death) that occurred between January 1, 2000 and December 31, 2005 were investigated and subsequently analyzed on demographic and clinical parameters of the deceased patients. The statistical analysis was performed as appropriate to illustrate any possible association between different demographic variables and SD. Results: There were 223 cases of SD (17.5%) out of 1273 total deaths in KFHU in the 6-year study period. There was a definite influence of age on the incidence of sudden death (SD) as it increased clearly at the two ends of the age spectrum, 32.2% of the cases were infants (from birth to 12 months), and 31.4% were elderly (> 60 year-old). However, among infantile age group, the highest frequency of SD (22.2% of the cases) was among the neonates. There was also a significant trend of gender influence on the incidence of SD which was higher in men than women (56% vs. 42%). The influence of prodromal symptoms and signs on SD was variable. Dyspnea and cough as major symptoms of cardiovascular and respiratory disease were the most frequent presenting symptoms in 32.3% of the cases, followed by fever as a sign of infections in 11.7%, premature infants in 10.8%, circulatory collapse in 9.4%, and angina in 7.6% of the cases. Conclusion: The current study indicated a definite influence of age, gender and prodromal symptoms on the incidence of SD. The highest incidence occurred in the two extremes of age scale as compared to other age groups. Incidence was also higher in men than women. Meanwhile, the major prodromal symptoms and signs were dyspnea and cough, fever, premature birth, circulatory collapse, and angina pectoris..